Tailor-made SCC incorporating spent equilibrium catalyst from oil refinery - Nunes, Sandra (2019)
The spent equilibrium catalyst (ECat) is a waste generated by the oil-refinery industry with very high pozzolanic activity and, therefore, has a great potential as an addition in SCC. This paper describes research on the use of factorial Design of Experiments (DoE) approach to design SCC mortar mixtures incorporating ECat. As such, a central composite design was carried out to mathematically model the influence of mixture parameters and their coupled effects on deformability, viscosity, compressive strength, resistivity and ultrasonic pulse velocity. Thereafter, a numerical optimization technique was applied to the derived models to select the best mixture, which simultaneously maximizes different engineering properties and eco-efficiency, while maintaining self-compactability.